2018
DOI: 10.1128/jvi.01174-18
|View full text |Cite
|
Sign up to set email alerts
|

Role of Capsid Anchor in the Morphogenesis of Zika Virus

Abstract: The flavivirus capsid protein (C) is separated from the downstream pre-membrane (PrM) protein by a hydrophobic sequence named capsid anchor (Ca). During polyprotein processing, Ca is sequentially cleaved by the viral NS2B/NS3 protease on the cytosolic side and by signal peptidase on the luminal side of the ER. To date, Ca is considered important mostly for directing translocation of PrM into the ER lumen. In this study, the role of Ca in the assembly and secretion of ZIKV was investigated using a pseudovirus-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 52 publications
3
37
0
Order By: Relevance
“…In the case of pestivirus, among five SPase target sites within the C–E rns –E1–E2–p7–NS2 region, E rns –E1 and E2–p7 processing are delayed and/or incomplete [ 17 , 18 , 19 ] ( Figure 1 C). Recent studies indicate that altering the SPase-mediated processing efficiency at these “delayed” cleavage sites reduced virus assembly and/or release, suggesting that maintaining the “optimal inefficiency” of SPase-mediated cleavage at these sites is essential for viral propagation [ 11 , 16 , 18 , 20 , 21 , 22 , 23 ]. By discussing recent progress, this review aims to provide insight on how different viruses within the Flaviviridae family differentially regulate the host SPase-mediated cleavage at specific junction site(s) within viral structural protein precursors and how the calculated regulation of SPase processing at these sites contributes to their efficient propagation.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of pestivirus, among five SPase target sites within the C–E rns –E1–E2–p7–NS2 region, E rns –E1 and E2–p7 processing are delayed and/or incomplete [ 17 , 18 , 19 ] ( Figure 1 C). Recent studies indicate that altering the SPase-mediated processing efficiency at these “delayed” cleavage sites reduced virus assembly and/or release, suggesting that maintaining the “optimal inefficiency” of SPase-mediated cleavage at these sites is essential for viral propagation [ 11 , 16 , 18 , 20 , 21 , 22 , 23 ]. By discussing recent progress, this review aims to provide insight on how different viruses within the Flaviviridae family differentially regulate the host SPase-mediated cleavage at specific junction site(s) within viral structural protein precursors and how the calculated regulation of SPase processing at these sites contributes to their efficient propagation.…”
Section: Introductionmentioning
confidence: 99%
“…Our efforts were concentrated on identifying myriad of potent anti-ZIKV clones that bind to the prM and envelope regions of ZIKV to mainly affect receptor binding targeting Domain III of envelope as well as the stem and transmembrane regions that alter virion entry, assembly, and membrane fusion. 42,43 Yet other structural and non-structural proteins may also be targeted to prevent or treat ZIKV infections. Monoclonal antibodies binding to ZIKV-NS1 region may confer advantages during an active viral replication phase of ZIKV infection, whereas clones that bind to ZIKV capsid anchor (Ca) region may block proper virion assembly as the cis-binding of Ca with PrM is strictly required to produce infectious particles.…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal antibodies binding to ZIKV-NS1 region may confer advantages during an active viral replication phase of ZIKV infection, whereas clones that bind to ZIKV capsid anchor (Ca) region may block proper virion assembly as the cis-binding of Ca with PrM is strictly required to produce infectious particles. 42 Broadly neutralizing capability of these anti-ZIKV clones has not been evaluated in this study since the dMAb-administered animals were challenged with a single strain of ZIKV-PR209. Despite the limitations in study designs, ZIKV has limited strain variability in which the African and Asian/American lineages are classified as a single serotype.…”
Section: Discussionmentioning
confidence: 99%
“…To understand the effect of unprocessed C-Ca on the production and infectivity of DENV2 particles, we initially used a tripartite system for the production of infective pseudoviruses as previously described [15]. The DENV2 capsid constructs used in this study, namely, mature C or C-Ca with either wild-type (T101) or mutated Ca (T101G) showed comparable efficiency in the production of infective pseudoviral particles, unlike other flaviviruses reported to have diminished effect on viral production in similar assays [14,31].…”
Section: Discussionmentioning
confidence: 99%
“…We are hereby referring to C as the mature capsid protein cleaved from Ca. We first implemented a tripartite complementation approach, as previously described [15], that uses three transcription units: (i) a WNV replicon (that contains an EGFP reporter) and (ii) two trans-packaging constructs encoding, one, the structural proteins PrME and, the other, the capsid, either in the mature processed form (called soluble C) or the anchored, unprocessed form (C-Ca) (scheme shown in Figure 1a). Two versions of the anchored capsid C-Ca were used: one that was not cleaved by the WNV protease, where the first amino acid of Ca was Thr(T101), and one carrying the T101G mutation that was cleaved by the WNV protease (termed, respectively, C-Ca T and C-Ca G (Figure 1a).…”
Section: Unprocessed Capsid Of Denv2 Does Not Affect Viral Infectivitymentioning
confidence: 99%